2019
DOI: 10.1108/jhti-06-2018-0034
|View full text |Cite
|
Sign up to set email alerts
|

Residents as destination advocates: the role of attraction familiarity on destination image

Abstract: Purpose Emphasizing the role of residents as destination advocates, the purpose of this paper is to investigate the influence of residents’ familiarity with, and, favorability of attractions on destination image. Design/methodology/approach A mixed methods research strategy was employed using 15 individual in-depth interviews and a survey questionnaire with a sample of n=364. The study utilizes an attraction familiarity index to classify respondents into four groups based on high, average, and low familiarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…In this context, the scientific understanding of the impact of particular elements and their familiarity on perceived attractiveness of the destination is crucial. Among rare examples of works deliberating the relationships between individual elements of a destination and the perception of this destination, the paper produced by Kessign et al [72] can be highlighted. The cited authors turned our attention to the importance of attractions located in a destination in the stated context, but the subject of the research was the residents' familiarity with attractions and how it influences the overall destination image.…”
Section: Perceived Attractiveness and Destination Familiaritymentioning
confidence: 99%
“…In this context, the scientific understanding of the impact of particular elements and their familiarity on perceived attractiveness of the destination is crucial. Among rare examples of works deliberating the relationships between individual elements of a destination and the perception of this destination, the paper produced by Kessign et al [72] can be highlighted. The cited authors turned our attention to the importance of attractions located in a destination in the stated context, but the subject of the research was the residents' familiarity with attractions and how it influences the overall destination image.…”
Section: Perceived Attractiveness and Destination Familiaritymentioning
confidence: 99%
“…They concluded that to a large extent, the determinants of tourism specialization in most developed countries were the same as those of intra-industry trade of commodities. Kesgin (2019) pointed out that the hospitality of residents in tourist destinations had a positive effect on the destination image. Some scholars conducted empirical analysis on the factors affecting the tourism service trade competitiveness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The recent study of Shoeb-Ur-Rahman et al (2020) discusses sustainable tourism development, including the notions of tourism capitals, sustainable livelihoods, quality of life and community well-being. The study of Kesgin et al (2019) emphasizes the destinations' development toward becoming an economic power with key destination attractions. In another study, Boley et al (2017) indicate that the following considerations are important for sustainable tourism development: "understanding the environmental, economic, and social sustainability features from the view of policymakers, conservation specialists, private businesses, and the locals who should interact and reach common ground to ensure the success of a destination."…”
Section: Introductionmentioning
confidence: 99%